Genetic diversity analysis of major Sri Lankan goat populations using microsatellite and mitochondrial DNA D-loop variations - Silva, P.; Dematawewa, C.M.B.; Kurukulasuriya, M.; Yuri T. Utsunomiya; García, J.F.; Pichler, R.; Thiruvenkadan, A.K.; Ramasamy, S.; Han Jianlin; Periasamy, K. (Elsevier, 2017)
The present study aimed at the genetic characterization of five major goat populations of Sri Lanka including four indigenous populations (Jaffna Local – JFL, Kottukachchiya – KOT, Southern – SLS and North Central – SNC) and one stabilized crossbred (German Boer x indigenous goats, also known as “Sri Lankan Boer” – SLB). Genetic diversity was evaluated using 15 microsatellite markers and the mitochondrial DNA D-loop variation. Allelic diversity and observed and expected heterozygosities were moderate, but less than Eurasian and Indian goat breeds. The overall mean estimated inbreeding coefficient (FIS) was 0.069 and significant heterozygote deficiency was detected in JFL (P < 0.001), KOT (P < 0.01) and SLS (P < 0.05), indicating population-specific drift or selection of the loci assessed. Genetic differentiation among populations was low and the phylogenetic clustering pattern was in line with the geographical location of goat populations. Although pair-wise Cavalli-Sforza and Edwards chord distance clustered SLS and SLB separately from the rest of the populations, Bayesian clustering clearly showed lack of discrete genetic structure in Sri Lankan goat populations despite significant morphological and phenotypic differences among them. Mitochondrial DNA D-loop sequences revealed significantly high haplotype diversity with the existence of maternal haplogroups ‘A’ and ‘B’. Analysis of mtDNA sequences indicated maternal origins of Jaffna Local, Kotukachchiya and Sri Lankan South distinct from the other goat populations.